A lightweight thermal heat switch for redundant cryocooling on satellites. (April 2017) - Dietrich, M.; Euler, A.; Thummes, G.
Highlights: Passive heat switch based on the high CTE of a thermoplastic (UHMW-PE). Improved design with respect to stability and thermal properties. Proven long term stability of the switching temperature. Proven mechanical stability of the switch construction. Abstract: A previously designed cryogenic thermal heat switch for space applications has been optimized for low mass, high structural stability, and reliability. The heat switch makes use of the large linear thermal expansion coefficient (CTE) of the thermoplastic UHMW-PE for actuation. A structure model, which includes the temperature dependent properties of the actuator, is derived to be able to predict the contact pressure between the switch parts. This pressure was used in a thermal model in order to predict the switch performance under different heat loads and operating temperatures. The two models were used to optimize the mass and stability of the switch. Its reliability was proven by cyclic actuation of the switch and by shaker tests.